STRATEGI PEMASARAN SAYUR KEMAS SIAP MASAK (VEGETABLE MIX) DI UMKM PACK INSTAN - Dheny Arina Hartawaty; Marosimy Millaty; Hermiza Aulia (Fakultas Pertanian Universitas Janabadra, 2025)
This study aims to explore information related to the general description of Pack Instan UMKM, the marketing approach applied to ready-to-cook packaged vegetable products, and identify the marketing methods considered most effective. The study was conducted using a case study approach accompanied by descriptive analysis to evaluate the implementation of various marketing strategies. The data collected in this study included primary and secondary sources. The results of the study revealed that Pack Instan UMKM uses four main approaches in marketing strategies, namely product strategy, pricing, distribution, and promotion. Among the four, the promotion has proven to be the most successful step in supporting sales, followed by product strategy, then pricing strategy, and finally distribution. In addition, this study also found several challenges faced in implementing the marketing strategy. These obstacles include production problems, difficulties in setting competitive prices, managing distribution channels, and obstacles in running effective promotions. Various efforts have been made to overcome these obstacles, providing insight for the development of better strategies in the future.